2001
DOI: 10.1002/app.1273
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of polyetherols from melamine and ethylene carbonate

Abstract: Attempts to synthesize s-triazine ring containing polyetherols from melamine and ethylene carbonate are described. The conditions of synthesis providing optimal yields of the polyetherols were 165°C, melamine to ethylene carbonate molar ratio 1 : 9 to 1 : 18, and 4 g of potassium carbonate or diazabicyclo[2.2.2]octane catalyst per mole of melamine. The structure of the products was established by 1 H-NMR and IR spectroscopy. The kind and amount of side products [mostly poly(ethylene glycols)] was determined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 6 publications
3
45
0
3
Order By: Relevance
“…In separate control experiments the products of EC with reference diols like glycol and polyglycols were analyzed chromatographically (Table 1). It has been found that the percentage of glycols and their consecutive products did not exceed 20 mass % in the products (Table 3), which is comparable to that found previously in case of melamineethylene carbonate system [31]. The presence of low molecular products in oligoetherol corroborates well with hydroxyl number (Table 2) which is 806.8 mg KOH/g, i.e., higher than the theoretical (602.6 mg KOH/g).…”
Section: Resultssupporting
confidence: 85%
“…In separate control experiments the products of EC with reference diols like glycol and polyglycols were analyzed chromatographically (Table 1). It has been found that the percentage of glycols and their consecutive products did not exceed 20 mass % in the products (Table 3), which is comparable to that found previously in case of melamineethylene carbonate system [31]. The presence of low molecular products in oligoetherol corroborates well with hydroxyl number (Table 2) which is 806.8 mg KOH/g, i.e., higher than the theoretical (602.6 mg KOH/g).…”
Section: Resultssupporting
confidence: 85%
“…Calibration curves for the chromatographic determinations (glycols and polyglycols) were used as described in the literature. 8 The reference substances were propane-1,2-diol, 4-oxaheptane-2,6-diol (OHD), 2-methyl-3-oxahexane-1,5-diol (MOHD), and 5-methyl-4,7-dioxadecane-2,9-diol (MDODD).…”
Section: Methodsmentioning
confidence: 99%
“…Also, IA slowly dissolved in PC within 35 h. The solid admixture was also present when mixtures of catalysts were used. Therefore, other catalysts were eventually chosen, including DABCO and TBAH (Table I, syntheses 5-9), which were successfully used before for the reactions of alkylene carbonates with melamine 8 and uric acid. 10 These catalysts allowed us to avoid the formation of solid admixtures, resulted in shorter procedures, and last, but not least, were cheaper.…”
Section: Synthesis Of the Polyetherols And Their Propertiesmentioning
confidence: 99%
“…Evidently, a more effective catalyst was needed. Basing on experience from studies on melamine oxyalkylation, 9 DABCO was selected as a catalyst. This catalyst used in DMF solution proved to be more effective than TEA.…”
Section: Figurementioning
confidence: 99%